Anti-inflammatory Activity of Salicylanilide Compounds from Gondopuro Oil as an In-Vitro - Koes Sundoro, Aries; Adhityasmara, Dhimas; Indriyanti, Erwin (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2023)
A component of gondopuro oil is methyl salicylate. Methyl salicylate has functional groups that allow it to be reformed. Changes in functional groups can occur through chemical reactions, one of which is through the aminolysis reaction to produce salicylamide or salicylanilide. The precursor for the synthesis of amide derivatives is a carboxylic acid, using natural methyl salicylate from gondopuro oil and amines sonochemically using sonichemical methods for 3, 4, and 5 hours with temperature control of ± 60ºC. Then liquid extraction was carried out using of hexane and distilled water 2 to 3 times until 2 phases were formed, then left for 1 night at a temperature of less than 100C and decanted. Then extracted with 10 mL of cold 5% NaOH 2 times until two phases were formed, namely the n-hexane fraction and the NaOH fraction. The NaOH fraction obtained is then heated using a water bath to evaporate the solvent so that it becomes a solid, which is then placed in an oven to form crystals. The crystals obtained were then dried using an oven at 40ºC until dry, and then the yield of the synthesized powder was calculated. From the research results, it can be concluded that Salicylanilide compounds can be synthesized using sonochemical methods and produce the largest % yield in the 3rd sample at 5 hours at 11.23%. Salicylanilide compounds have anti-inflammatory activity at a concentration of 100.0 ppm with a % inhibition of 46.07%.